Unusual expansion of Laurencia obtusa (Hudson) J.V. Lamouroux in the Zambratija Bay (northern Adriatic Sea) - Orlando-Bonaca, Martina (Annales. Series historia naturalis, 2017)
The paper reports an unusual expansion of the red alga Laurencia obtusa in shallow waters of the Zambratija Bay (northern Adriatic Sea). The large population of L. obtusa was never observed during underwater surveys conducted in recent years. In this area, benthic communities dominated by brown algae from the genus Cystoseira were present. The authors therefore assume that some environmental factors have probably changed and have favoured the extension of this red alga. The hypothesis for this phenomenon takes into account the possibility that the establishment of the invasive green alga Caulerpa cylindracea in the Zambratija bay has had a negative impact on native macroalgal assemblages.
Keywords: Adriatic Sea; algae; alge; Laurencia obtusa; monospecific populations; obalno morje; pojavljanje; rdeče alge; shallow waters; Zambratija Bay